2012
DOI: 10.1177/0885728812443082
|View full text |Cite
|
Sign up to set email alerts
|

Using Video Modeling Delivered Through iPods to Teach Vocational Tasks to Young Adults With Autism Spectrum Disorders

Abstract: The purpose of this study was to evaluate the effectiveness of using video modeling delivered through a portable media player (Apple video iPod) as a means of teaching job-related tasks to four young adults with autism spectrum disorders. The videos were enhanced by adding written instructions. Results indicated that using the iPod was associated with immediate and substantial gains in the percentage of steps completed correctly. All of the participants demonstrated maintenance of the acquired tasks. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
70
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 15 publications
6
70
0
4
Order By: Relevance
“…In this study, point-of-view video models depicted the steps to be performed in an ADL task along with a verbal description of each step. The data in this study support Kellems and Morningstar (2012) and previous video-modeling research in which the use of video modeling has been shown to be effective with teaching ADLS and other skills such as vocational, social, and transitional skills.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…In this study, point-of-view video models depicted the steps to be performed in an ADL task along with a verbal description of each step. The data in this study support Kellems and Morningstar (2012) and previous video-modeling research in which the use of video modeling has been shown to be effective with teaching ADLS and other skills such as vocational, social, and transitional skills.…”
Section: Discussionsupporting
confidence: 73%
“…This study extends the work of Kellems and Morningstar (2012) in several notable ways. First, we employed a more stringent mastery criterion.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations